Stress Ocupacional em Bombeiros: estudo da versão portuguesa do Perceived Work Related Stress Questionnaire - Murillo, Maria Margarida Reis (2021)
Objetivos: Este estudo pretendeu analisar a estrutura fatorial e propriedades psicométricas da versão portuguesa do Perceived Work-related Stress Questionnaire (PWSQ) numa amostra de bombeiros. Método: A amostra integrou 155 bombeiros de várias corporações, que completaram online os instrumentos de autorresposta: Perceived Work-related Stress Questionnaire; Patients Health Questionnaire-4 (PHQ-4); Perceived Stress Scale (PSS); World Health Organization Index-5 (WHO-5). Foi realizada uma análise fatorial confirmatória (AFC) e conduzidos estudos de fidedignidade e validade. Resultados: A AFC do modelo unidimensional do PWSQ (com especificação de correlações entre dois pares de itens), evidenciou um bom ajustamento aos dados. A medida apresentou consistência interna adequada (alfa de Cronbach de .75 e fiabilidade compósita de .76). As correlações com outros instrumentos foram sugestivas de validade concorrente e incremental. Não foram encontradas diferenças estatisticamente significativas nos valores médios do PWSQ em função do sexo e grupos de antiguidade profissional. Não se verificaram associações com a idade e os anos de escolaridade. Conclusões: A versão portuguesa do PWSQ evidenciou-se como uma medida fiável, breve e psicometricamente válida para avaliar o stress ocupacional em bombeiros. A disseminação e uso desta medida poderá contribuir para uma avaliação mais rigorosa do stress ocupacional, assim como da eficácia de programas de intervenção. / Aims: This study aimed to analyze the factor structure and psychometric properties of the Portuguese version of the Perceived Work-related Stress Questionnaire (PWSQ) in a sample of firefighters. Method: The sample comprised 155 firefighters from several fire stations, who completed online a set of self-report instruments: Perceived Work-related Stress Questionnaire; Patients Health Questionnaire-4 (PHQ-4); Perceived Stress Scale (PSS); World Health Organization Index-5 (WHO -5). A confirmatory factor analysis (CFA) was computed, and reliability and validity studies were conducted. Results: The single-factor model (encompassing the specification of correlations between two pairs of items residuals) CFA results revealed a good fit to the data. The PWSQ showed an adequate internal consistency (Cronbach's alpha of .75 and a composite reliability of .76). Correlations results with other variables were suggestive of concurrent and incremental validity. No statistically significant differences were found in the PWSQ mean scores between men and women and time of service groups. There were no associations between the PWSQ and age or years of education. Conclusions: The PWSQ Portuguese version showed to be a reliable, brief and psychometrically valid measure to assess firefighters’ occupational stress. Its dissemination and use may contribute to a more rigorous assessment of occupational stress, as well as the efficacy of intervention programs.